Slovenski duhovniki v času pred koroškim plebiscitom - Kolar, Bogdan (Studia Historica Slovenica, 2025)
Slovenian priests, who worked mainly in the southern part of the diocese of Krka/Celovec, were subjected to various forms of pressure during the First World War. Legal proceedings were prepared against them. This paper shows the role that priests played in the period before the plebiscite, as they were closely involved in events in the two years before the plebiscite and almost unanimously supported the decision that the plebiscite area should become part of the new South Slavic state. This brought them a lot of opposition and even threats from the German-oriented population and state structures. Even the local bishop was not sympathetic to them. Several priests had the opportunity to participate in the international political arena. In addition to official documents, memoirs and parish chronicles from the plebiscite area are of great historical value.
Keywords: Carinthia; clergy; duhovščina; ethnic hatred; Koroška; narodnostno sovraštvo; parishes; plebiscit; plebiscite; župnije